CLEAR-CUTTING OF ACACIA PLANTATION IN A HEADWATER CATCHMENT OF VIETNAM: ENVIRONMENTAL IMPACTS AND SOLUTIONS FOR SUSTAINABLE MANAGEMENT - Xuan Dung, Bui; Thi Tra My, Tran; Thuy Oanh, Kieu; Thanh Tu, Tran; Duc Tri, Trieu; Kyaw, Sandar (Journal of Forestry Science and Technology, 2023)
To assess impacts of clear-cutting at a pure Acacia plantation on soil and water quality, a 7-year-old Acacia forest within the area of 2.5 ha in Hoa Binh province was selected to investigate at 2 stages: before and after clear-cutting. 03 standard plots (500 m2/plot) at 3 positions (downhill, mid-hill and top-hill) for determining forest characteristics, 30 sampling subplots (1 m2/plot) for monitoring forest covers and some soil properties. 15 of 30 subplots were used to measure infiltration; and 4 points along forest flow were chosen to take water sampling for assessing water quality. Main findings include: (1) Forest cover decreased within the removal of tree, reduction of understory vegetation cover, litter and biomass ranged from 10 to 20%; (2) Soil quality decreased by 8.35% dropped of porosity due to the rise of 8.57% in dry bulk density; (3) Soil nutrients: Organic matter, total Phosphorus and Nitrogen amount decreased at the proportion of 20.91%, 62.86% and 27.86% respectively after clear-cutting; (4) Total infiltration rate decreased after harvesting. The positions that had high infiltration rate before clear-cutting tended to infiltrate noticeably less (Downhill: reducing from 397.7 mm to 201.2 mm); (5) Soil erosion increased significantly after cutting and was remarkably higher in comparison with other research results due to the slope of researching area; (6) Most water quality indicators were at acceptable values, however, TSS and COD were 180-time and 5.6-time higher than water standard at B1 category (water for irrigation) according to QCVN 08:2015/BTNMT; (7) Some solutions suggested for sustainable management are (a) replacing production planted forest at researching site by protection forest or natural forest or (b) remaining commercial plantation forest but adjust management methods.